2016
DOI: 10.1523/jneurosci.4329-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

AMPA-Kainate Receptor Inhibition Promotes Neurologic Recovery in Premature Rabbits with Intraventricular Hemorrhage

Abstract: Intraventricular hemorrhage (IVH) in preterm infants leads to cerebral inflammation, reduced myelination of the white matter, and neurological deficits. No therapeutic strategy exists against the IVH-induced white matter injury. AMPA-kainate receptor induced excitotoxicity contributes to oligodendrocyte precursor cell (OPC) damage and hypomyelination in both neonatal and adult models of brain injury. Here, we hypothesized that IVH damages white matter via AMPA receptor activation, and that AMPA-kainate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…To determine whether USSCs affected cytokine expression in IVH‐induced inflammation, we measured mRNA expression of relevant cytokines in our rabbit model of IVH: IL1‐β and TNFα using qPCR. Consistent with our previous reports, the mRNA levels of IL1‐β and TNF‐α were significantly elevated in pups with IVH compared with no IVH controls at day 3 (Fig. D, E; p < .05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether USSCs affected cytokine expression in IVH‐induced inflammation, we measured mRNA expression of relevant cytokines in our rabbit model of IVH: IL1‐β and TNFα using qPCR. Consistent with our previous reports, the mRNA levels of IL1‐β and TNF‐α were significantly elevated in pups with IVH compared with no IVH controls at day 3 (Fig. D, E; p < .05).…”
Section: Resultsmentioning
confidence: 99%
“… In our previous studies, we demonstrated suppression of inflammation followed by improved myelination and less gliosis using various pharmacological approaches indicating some degree of injury was reversible. Therefore, in the present study, we examined the same regions of the CR and CC (Fig. S4).…”
Section: Discussionmentioning
confidence: 99%
“…Increased cell death and apoptosis have been evidenced by TUNEL staining and CASP3 activation in the periventricular WM (Dummula et al, 2011;Ahn et al, 2013;Gram et al, 2014;Dohare et al, 2016;Mukai et al, 2017) and adjacent GM [striatum (Xue et al, 2003) or cortex (Georgiadis et al, 2008;Zia et al, 2009;Vinukonda et al, 2010)]. However, the identification of the dying cells has not been determined except in some studies showing that cell death (Fluoro-Jade+ cells) could affect O4+ pre-oligodendrocytes or neurons.…”
Section: Preclinical Models Of Intraventricular and Intraparenchymatomentioning
confidence: 99%
“…thrombin, fibrinogen, hemoglobin). After IVH there is an upregulation of pro-inflammatory cytokines, microglial activation and leukocyte infiltration into brain 110, 111 . Microglia are the resident brain immune cells that upon activation can have a range of phenotypes.…”
Section: Ivh-induced Brain Injurymentioning
confidence: 99%